Feasibility of a Home-Based Tablet App for Dexterity Training in Multiple Sclerosis: Usability Study - van Beek, Judith Jantine Willemijn; van Wegen, Erwin Everardus Henri; Rietberg, Marc Berend; Nyffeler, Thomas; Bohlhalter, Stephan; Kamm, Christian Philipp; Nef, Tobias; Vanbellingen, Tim (JMIR Publications, 2020)
BackgroundPersons with multiple sclerosis (MS) often experience dexterous difficulties during the performance of activities of daily living, such as fastening buttons, handling coins, or writing, therefore impacting their health-related quality of life. Mobile health (mHealth) solutions, such as tablet apps, may be used to train impaired dexterous skills. The feasibility of a tablet app-based dexterity home-based intervention in MS (TAD-MS) has not been explored yet in persons with MS. ObjectiveThe aim of this pilot study was to evaluate the feasibility and usability of home-based dexterity training with a tablet app in both persons with MS and healthy subjects. MethodsA total of 9 persons with MS, aged 35-71 years, with an Expanded Disability Status Scale score between 2 and 7.5, performed the TAD-MS for 4 weeks, five times a week, with each training session lasting approximately 30 minutes. Participants' impaired dexterity was measured by the Nine-Hole Peg Test. A total of 10 age-matched healthy subjects also tested and rated the usability of the app. Outcome measures were the adherence rate as well as usability measured by the System Usability Scale and a Custom User Engagement Questionnaire (CUEQ). ResultsHigh feasibility of the tablet app-based dexterity training program was shown by a 97% adherence rate to the training protocol (ie, mean 19.4/20 sessions completed, SD 0.8). High system usability scores (ie, mean 85.39%, SD 11.67) and overall high scores given in the CUEQ (ie, mean 8.2/10, SD 1.4) further point to high usability of the app. Neither demographic variables nor dexterity levels affected the use of the app. ConclusionsThis pilot study is the first to demonstrate high feasibility and usability of a new tablet app-based dexterity home-based training program among both persons with MS and healthy individuals. Whether this kind of training improves dexterity will need to be evaluated in a randomized controlled trial.